International Debt Statistics 2016 - World Bank Group (Washington, DC: World Bank, 2015)
International Debt Statistics (IDS) 2016 (formerly Global Development Finance) provides statistical tables showing the external debt of 125 developing countries that report public and publicly guaranteed external debt to the World Bank's Debtor Reporting System (DRS). It also includes tables of key debt ratios for individual reporting countries and the composition of external debt stocks and flows for individual reporting countries and regional and income groups, along with some graphical presentations.